2013
DOI: 10.1155/2013/819531
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid, Polyamines, and Phenols in Hardwood Cuttings of Recalcitrant-to-Root Wild Grapes Native to East Asia:Vitis davidiiandVitis kiusiana

Abstract: Levels of indole-3-acetic acid (IAA), free, conjugated, and bound polyamines (PAs), and phenols were estimated in the basal portion of hardwood cuttings ofVitis davidiiandV. kiusianain relation to rooting and compared withVitis labruscanaBailey cv. Campbell Early. A high rate of root formation was observed in ‘Campbell Early’ cuttings 60 days after planting. However, none of theV. davidiiandV. kiusianacuttings formed roots. An increase in IAA contents was observed in ‘Campbell Early’ cuttings, but not inV. dav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, adventitious roots are di cult to be induced in many grape species or varieties with important breeding utilization, such as V. davidii, V. quinquangularis (syn. V. kiusiana), and V. amurensis which are wild grapes native to East Asia (Shiozaki et al 2013). The V. rotundifolia (Muscadine) (Castro et al 1994), V. champinii (Saleh 2019), V. aestivalis (Keeley et al 2004), V. berlandieri (Kracke et al 1981;Smart et al 2003), and some cultivars of V. vinifera are also known to be di cult to root from their woody cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…However, adventitious roots are di cult to be induced in many grape species or varieties with important breeding utilization, such as V. davidii, V. quinquangularis (syn. V. kiusiana), and V. amurensis which are wild grapes native to East Asia (Shiozaki et al 2013). The V. rotundifolia (Muscadine) (Castro et al 1994), V. champinii (Saleh 2019), V. aestivalis (Keeley et al 2004), V. berlandieri (Kracke et al 1981;Smart et al 2003), and some cultivars of V. vinifera are also known to be di cult to root from their woody cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] or Vitis vinifera [ 27 ], we found no correlation between callus size and AR number, suggesting that these two processes (callus growth and establishment of AR primordia) could be regulated independently in Prunus rootstocks. Indeed, studies conducted on grape rootstocks also confirmed the independent regulation of callus and AR formation in this species [ 28 ]. The rooting of hardwood cuttings from Garnem and GF 677 differed mainly in the timing of AR formation, resulting in a significantly higher number of ARs in Garnem.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, Somkuwar et al (2011) reported that high levels of phenols in grape rootstock cuttings at planting may be correlated with the formation of root primordia and stimulate the elongation of the roots. With respect to the phenols type, some phenolic compounds had a positive effect such as phloroglucinol and chlorogenic acid on rooting (Wilson and Van Staden, 1990, Wang 1991and Shiozaki et al, 2013. Also, gallocatechin found in ‗Campbell Early' cuttings which may be prevent IAA oxidation.…”
Section: Discussionmentioning
confidence: 99%